Managements for Controlling Inflammation/ Infection in Diabetic Foot Ulcers: A Scoping Review - Ifadah, Erlin; Yamada, Amika; Aminuddin, Muhammad; Mukai, Kanae; Oe, Makoto (Indonesian Contemporary Nursing Journal (ICON Journal), 2026)
Aims: This review summarizes the management strategies for controlling inflammation/infection in diabetic foot ulcers based on infection severity and identifies research gaps. Methods: This scoping review was conducted in accordance with the PRISMA-ScR guidelines. Three databases (PubMed, CINAHL, and Medline) were searched in October 2024 using combinations of keywords related to diabetic foot ulcers, inflammation, infection, osteomyelitis, and management. Two independent researchers screened and extracted data from studies meeting the inclusion criteria: original articles/case reports, studies involving patients with diabetic foot ulcers, and studies on inflammation/infection management. Results: The search yielded 11201 articles, of which 206 met the inclusion criteria. The included studies were published between 1993 and 2024. Among these, two studies focused on inflammation and reported the beneficial effects of antioxidant vitamin and mineral supplementation and glycemic control. A total of 124 studies addressed infection management strategies, demonstrating the effectiveness of debridement, systemic antibiotic therapy, and adjunctive or innovative therapies. However, quantitative evidence distinguishing interventions based on local and systemic infections remains limited. In addition, 80 studies focused on osteomyelitis, supporting the effectiveness of surgical intervention, systemic antibiotic therapy, and adjuvant therapy.  Conclusion: The management strategies for diabetic foot ulcers include nutritional intervention, antimicrobial treatments, adjuvant therapies, and surgery. While these approaches affect inflammation and infection control, no study has identified the best method for each infection condition. Further research is needed to develop specific recommendations based on the infection severity and skin layers in diabetic foot ulcers.